Evaluation Of Jepara Regency Regulation Number 2 Of 2014 On The Existence Of Jepara Furniture Development In The 2021 Covid-19 Pandemic - Labiba, Niswa Adlina; Yuwono, Teguh; Martini, Rina (Universitas Muhammadiyah Jember Press, 2023)
The purpose of this study is to analyze and evaluate a policy of Jepara Regency Regional Regulation Number 2 of 2014 concerning the Protection, Empowerment, and Development of the Furniture Industry. This study uses a qualitative approach with data collection techniques in the form of interviews through snowball sampling techniques. This study uses William N. Dunn's public policy evaluation theory. The results of the study show that various kinds of problems have arisen, such as a decline in exports due to many destination countries being locked down, the difficulty in finding production workers, the scarcity of wood materials, to the lack of infrastructure and facilities from the government. Through this Regional Regulation, it has not been able to overcome all kinds of problems that occur optimally. Moreover, from the 6 indicators of policy evaluation according to William N. Dunn, this Regional Regulation can only carry out 2 optimal indicators. This study recommends that the government review the effectiveness of regional regulations. In addition, the government must also establish better cooperation with other actors such as furniture business associations and wood-producing regions to provide reciprocity and maintain the existence of Jepara furniture.